Effects of the anchor system on postural control in older Adults - Eliane Mauerberg de Castro; Victor Hugo Alves Okazaki; Juliana Bayeux Dascal (Universidade Federal de Santa Catarina, 2012)
Falls are common during aging, and can have drastic consequences. Within this context, maintaining the ability to balance plays an essential role in enabling older adults to continue to perform their daily activities. Therefore, the use of interventional and treatment tools for development of balance becomes essential. The objective of this study was to analyze the anchor system as a potential tool for decreasing body sway in older and young adults. Older adults had more postural sway than their young counterparts. The absence of visual information led to larger instability in both groups. The anchor system improved postural stability of both groups. Thus, it may be a useful tool for posture stabilization in old and young adults.